The effects of macroeconomic, fiscal and monetary policy announcements on sovereign bond spreads: an event study from the EMU - António Afonso; Jo\~ao Tovar Jalles; Mina Kazemi (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
We assess the impact of announcements corresponding to different fiscal and monetary policy measures on the 10-year sovereign bond yield spreads (relative to Germany) of the 10 EMU countries during the period 01:1999 - 07:2016. Implementing pooled and country-fixed effects OLS regressions, we find that the European Commission's (EC) releases of the excessive deficit procedure significantly affect the yield spreads. The EC releases of higher debt and better budget balance forecasts contribute to the rise and the decline of spreads, respectively. Moreover, we find that the announcements of the ECB's key interest rates together with the longer-term refinancing operations (LTROs) and the first covered bond purchase programme (CBPP1) negatively affect sovereign yield spreads in our sample of EMU countries.
Keywords: 330